Oxidative stress pathways in pancreatic β-cells and insulin-sensitive cells and tissues: importance to cell metabolism, function, and dysfunction - Newsholme, Philip; Keane, Kevin N; Carlessi, Rodrigo; Cruzat, Vinicius (American Journal of Physiology: Cell Physiology, 2019)
It is now accepted that nutrient abundance in the blood, especially glucose, leads to the generation of reactive oxygen species (ROS), ultimately leading to increased oxidative stress in a variety of tissues. In the absence of an appropriate compensatory response from antioxidant mechanisms, the cell, or indeed the tissue, becomes overwhelmed by oxidative stress, leading to the activation of intracellular stress-associated pathways. Activation of the same or similar pathways also appears to play a role in mediating insulin resistance, impaired insulin secretion, and late diabetic complications. The ability of antioxidants to protect against the oxidative stress induced by hyperglycemia and elevated free fatty acid (FFA) levels in vitro suggests a causative role of oxidative stress in mediating the latter clinical conditions. In this review, we describe common biochemical processes associated with oxidative stress driven by hyperglycemia and/or elevated FFA and the resulting clinical outcomes: β-cell dysfunction and peripheral tissue insulin resistance.